1996
DOI: 10.1016/0048-9697(96)05162-5
|View full text |Cite
|
Sign up to set email alerts
|

Mobility of Chernobyl-derived 137Cs in a peatbog system within the catchment of the Pripyat River, Belarus

Abstract: The behaviour of Chernobyl-derived 137Cs in a hydrologically isolated bog system in the catchment of the Pripyat River, Belarus was investigated. Measurements were made of 137Cs activities in the solids and pore waters of the bog soils, as well as the variability in activity in water draining from the bog. It was found that the radiocaesium activity of the pore water, and hence the measured distribution coefficient, Kd, was dependent upon the pressure at which the water was removed from the soil. Measured valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

1999
1999
2025
2025

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 6 publications
0
23
0
1
Order By: Relevance
“…larger than 10 Bq kg À1 ) can be observed below 30 cm, which is accounted by downward diffusion of this element in the peat. MacKenzie et al (1997) and Kudelsky et al (1996) reported the high mobility of this element in peats from Scotland and from the catchment of the Pripyat River (Belarus). The total accumulation of 137 Cs in the peat profile reaches 11,246 Bq m À2 .…”
Section: Distribution Of Radionuclides In Peatmentioning
confidence: 96%
“…larger than 10 Bq kg À1 ) can be observed below 30 cm, which is accounted by downward diffusion of this element in the peat. MacKenzie et al (1997) and Kudelsky et al (1996) reported the high mobility of this element in peats from Scotland and from the catchment of the Pripyat River (Belarus). The total accumulation of 137 Cs in the peat profile reaches 11,246 Bq m À2 .…”
Section: Distribution Of Radionuclides In Peatmentioning
confidence: 96%
“…Nuclide Range Unit n Sources Liquid wash-off 137 Cs 6.7 Â 10 À5 e0.02 /yr 62 Beasley and Jennings (1984), Bilyi et al (1997), Carlsson (1978), Kudelsky et al (1996), Linsley et al (1982), Rogowski and Tamura (1970) and Spezzano et al (1993) Liquid wash-off 90 Sr 6.7 Â 10 À4 e0.05 /yr 28 Helton et al (1985), Kamada et al (1974), Linsley et al (1982), Miyake and Tsubota (1963), Monte (1995), Pisarev et al (1972) and Yamagata et al (1963) Solid wash-off 241 Am 1 Â 10 À4 e2 Â 10 À4 /yr 2 Beasley and Jennings (1984) and Solid wash-off 7 Be 0.02 /yr 1 Joshi and Shukla (1991) Solid wash-off 137 Cs 8.9 Â 10 À5 e0.12 /yr 11 Beasley and Jennings (1984), Bonnett (1990), Dominik et al (1987), , Khanbilvardi et al (1999), Rogowski and Tamura (1970), Smith et al (1987) and Walling et al (1986) Solid wash-off 210 Pb 3.3 Â 10 À4 e7.14 Â 10 À4 /yr 2 Dominik et al (1987) and Joshi and Shukla (1991) Solid wash-off Pu 2 Â 10 À5 e6 Â 10 À3 /yr 36 Beasley and Jennings (1984), Bonnett (1990), Foster and Hakonson (1984), and Smith et al (1987) Total wash-off 137 Cs 3.75 Â 10 À5 e0.01 /yr 18 Beasley and Jennings (1984), Bonnett (1990), Ettenhuber et al (1990), Kudelsky et al (1997), Linsalata et al (1985), Matsunaga (2000), Queirazza et al (1987), Smith et al (2000), Spezzano et al (1994) and Yamagata et al (1963) …”
Section: Processmentioning
confidence: 99%
“…The mobility of ,37 Cs essentially depends on the concentration of K + and NH/ in water phase [3,4]. These cations compete with 137 Cs for FES and increase caesium transfer from solid phase into interstitial soil solution and NFL/ is more selective to FES than K + .…”
Section: Resultsmentioning
confidence: 99%